2003
DOI: 10.1128/iai.71.8.4742-4748.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inactivation of the Arg- and/or Lys-Gingipain Gene on Selected Virulence and Physiological Properties of Porphyromonas gingivalis

Abstract: Proteolytic enzymes produced by Porphyromonas gingivalis are thought to play critical roles in the pathogenesis of periodontitis. The aim of this study was to investigate the effect of gingipain cysteine proteinase gene inactivation on selected pathological and physiological functions of P. gingivalis. Our results showed that Argand Lys-gingipain activities are critical components for the efficient growth of P. gingivalis in human serum. However, when the serum was supplemented with peptides provided as pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 44 publications
3
70
3
1
Order By: Relevance
“…The authors suggest that lysis is prevented by the presence of anionic polysaccharides on a bacterial surface. The results of this study are in contrast with other published results that showed that a P. gingivalis mutant lacking all three gingipains was extremely sensitive to lysis by complement (30). In direct contrast, a mutant lacking HRgpA and RgpB was reported to survive in NHS equally well as the wild type (20) or to survive at 28% as compared with 87% for the wild type (30).…”
Section: Discussioncontrasting
confidence: 99%
“…The authors suggest that lysis is prevented by the presence of anionic polysaccharides on a bacterial surface. The results of this study are in contrast with other published results that showed that a P. gingivalis mutant lacking all three gingipains was extremely sensitive to lysis by complement (30). In direct contrast, a mutant lacking HRgpA and RgpB was reported to survive in NHS equally well as the wild type (20) or to survive at 28% as compared with 87% for the wild type (30).…”
Section: Discussioncontrasting
confidence: 99%
“…Proteases and fimbriae produced by P. gingivalis cause inflammation in mammalian models (15,(23)(24)(25). We tested the killing effects of heat-treated mutant strains of P. gingivalis that lack genes encoding these virulence factors.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilm formation was assayed in 96-well microtiter dishes made of polystyrene (Falcon 353936) using a slightly modified previously published protocol (29). In brief, THBHK (200 l/well) was inoculated from cells patched on BAPHK agar plates containing tetracycline.…”
Section: Methodsmentioning
confidence: 99%